Evaluating dried distillers grains with solubles or corn gluten feed as a replacement for soybean meal in Boer-type goat grower rations - Hissong, Claudia Elaine; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2019)
The Boer goat population in the United States has been increasing rapidly within the last decade, but there is little published research regarding the nutrition of this specie. Our research objective is to provide a better understanding of dried distillers grains with solubles (DDGS) or corn gluten feed (CGF) as a replacement for soybean meal (SBM) in Boer-type goat grower rations. Dried distillers grains with solubles and CGF are an inexpensive protein source relative to SBM and highly available. The research focuses on 5 dietary treatments. Treatments were isocaloric and isonitrogenous, but varied in protein source: 1) SBM; 2) 100% DDGS/0% CGF; 3) 66% DDGS/33% CGF; 4) 33% DDGS/66% CGF; 5) 0% DDGS/100% CGF. Seventy-Five Boer-type goats that weighed 26.9 ± .2 kg, were allotted to pens in a completely randomized design and fed for 35 days. Pen was the experimental unit, with 3 goats per pen and 5 pens per treatment. Goats and feeders were weighed weekly to evaluate ADG, ADFI, G:F, cost per kg of diet, and cost per kg of gain. Data was then analyzed using the GLIMMIX procedure of SAS with an alpha value of 0.05. There was no evidence (P>0.05) among the varying diets that impacted BW, ADG, ADFI, and G:F. However, there was evidence that the corn co-product feed was the less expensive (P=.001) feed cost per goat. There was no evidence (P=.94) that cost per kg of gain was less for goats fed the corn co-products. Therefore, producers can conclude there is not significant difference in growth performance in goats fed SBM, CGF, or DDGS as their protein source and can make their ration decision based on economics.
Keywords: Spring 2019